EXPLORATION OF THE ZOMBIE MYTHS FROM VOODOO TO UNIVERSAL HORROR: A PSYCHOANALYTICAL EVOLUTION IN SELECT MOVIES - Lakshmi R; Sheeba (International Journal of Research -GRANTHAALAYAH, 2025)
The zombie myth has changed greatly over the decades, from its origins in Haitian Voodoo, where it symbolized spiritual enslavement and colonialism, to its current status as a global icon of terror in popular culture. However, there is little psychological research examining the dynamics of this change. Most research dismisses the role those unconscious anxieties, such as losing one's humanity or identity, have had in the development of the zombie. This paper fills that gap by using psychoanalytic theory to examine how the zombie symbolizes societal anxieties, from its origins in Voodoo to its current status as a global symbol of fears. By connecting its historical and cultural roots to its modern-day representations, this research provides a deeper understanding of how the zombie has become a universal metaphor for human fears.